Hip morphology predicts posterior hip impingement in a cadaveric model. Issue 3 (May 2019) - Morris, William Z; Fowers, Cody A; Weinberg, Douglas S; Millis, Michael B; Tu, Leigh-Anne; Liu, Raymond W
Introduction: Posterior hip impingement is a recently-identified cause of hip pain. The purpose of this study is to characterise posterior femoroacetabular and ischiofemoral impingement and identify its predisposing morphologic traits. Methods: Two hundred and six cadaveric hips were randomly selected and taken through controlled motion in two pure axes associated with posterior hip impingement: external rotation (through the mechanical axis) and adduction (coronal plane). The range of motion and location of impingement was noted for each specimen. Morphologic traits including femoral/acetabular version, and true neck-shaft angle (TNSA) were also measured. Results: External rotation impingement occurred between the femoral neck and acetabulum in 83.0% of hips, and between the lesser trochanter and ischial tuberosity in 17.0%. Adduction impingement occurred between the lesser trochanter and ischial tuberosity in 78.6% of hips, and between the femoral neck and acetabulum in 21.4%. Multiple regression revealed that increased femoral/acetabular version predicted earlier external rotation and adduction impingement. Unstandardised betas ranging from −0.39 to −0.64 reflect that each degree of increased femoral/acetabular version individually accounts for a loss of external rotation or adduction of approximately half a degree before impingement ( p < 0.001 for each). Increased TNSA was associated with earlier adduction impingement only (unstandardised beta −0.35, p = 0.005). Discussion: Relative femoral/acetabular anteversion was associated with earlier posterior hip impingement. Coxa valga was associated with earlier adduction impingement, but protective against external rotation impingement. These findings highlight the importance of monitoring correction during femoral/acetabular osteotomies, as overcorrection of retroversion may predispose to earlier posterior impingement.